Staphylococcus aureus bacteremia complicated with non-traumatic mediastinal abscess in children: A case report - Yiyuan Li; Yu Zhu; Chaomin Wan; Yang Wen (Frontiers Media S.A., 2023)
BackgroundStaphylococcus aureus bacteremia complicated with non-traumatic mediastinal abscess rarely occurs in children. Herein, we report a case of S. aureus bacteremia in a previously healthy 15-month-old boy, which was complicated with a non-traumatic mediastinal abscess, followed by recovery without surgeryCase presentationA previously healthy 15-month-old boy presented to the hospital with a high fever, accompanied by chills, lethargy, tachycardia, tachypnea, and slight cough. Contrast-enhanced computerized tomography revealed mediastinal abscess and blood culture analysis showed the presence of S. aureus which was methicillin-susceptible. With prompt initiation of antibiotic treatment, with appropriate duration, the patient successfully recovered without surgical drainage upon discharge.ConclusionsStaphylococcus aureus bacteremia complicated with non-traumatic mediastinal abscess is rare in children, and early recognition and appropriate management are essential for a successful outcome.